7 Effects of Syngenta Enogen Feed Corn (SYT-EFC) and corn processing methods fed with byproducts on finishing cattle performance and carcass characteristics - Hopfauf, Stacia M (J Anim Sci, 2020)
The objective of this pooled analysis was to evaluate the effect of Syngenta Enogen Feed Corn (SYT-EFC) and corn processing methods with byproducts on finishing cattle performance and carcass characteristics. Treatment factors consisted of SYT-EFC or commercial corn (CON) processed as dry-rolled (DRC) or high-moisture corn (HMC). Byproduct comparisons were 0, 18, or 30% distillers grains inclusions or with 30% Sweet Bran to determine if SYT-EFC effect was impacted by byproducts. Seven trials (n = 2,340 steers; initial BW = 327 ± 20 kg) consisting of 252 pen means with 12 treatments were analyzed utilizing contrasts. Feeding SYT-EFC as DRC resulted in heavier final BW (P ≤ 0.03) and greater 12(th) rib fat (P < 0.01) compared to CON. There was a linear interaction between hybrid and distillers for G:F (P < 0.01). As distillers increased, G:F improved at a greater rate for CON compared to SYT-EFC. Feeding SYT-EFC as DRC with increasing distillers was not significantly different (P ≥ 0.68) from CON for G:F, but was 3% better than CON with 0% distillers. Feeding SYT-EFC as DRC with 18% distillers resulted in heavier final BW (P < 0.01) compared to 0 or 30% distillers. Feeding SYT-EFC as DRC with Sweet Bran resulted in heavier final BW (P ≤ 0.02) and greater ADG (P < 0.01) compared to CON. This increase in ADG with no difference in DMI, resulted in SYT-EFC diets having a 5.08% increase in feed efficiency (P < 0.01). The improvement for the corn is calculated to be 9.58% (5.08 / 0.53) when SYT-EFC was fed with Sweet Bran compared to a CON corn hybrid. No positive effects were observed when SYT-EFC was processed as HMC. These data suggest that SYT-EFC is better than CON hybrids when distillers inclusion is low or when fed with Sweet Bran.